Dynamic Conditional Beta Is Alive and Well in the Cross Section of Daily Stock Returns - Bali, Turan G.; Engle, Robert F.; Tang, Yi (Management Science, 2017)
This paper presents evidence for a significantly positive link between the dynamic conditional beta and the cross section of daily stock returns. An investment strategy that takes a long position in stocks in the highest conditional beta decile and a short position in stocks in the lowest conditional beta decile produces average returns and alphas in the range of 0.60%–0.80% per month. We provide an investor attention-based explanation of this finding. We show that stocks with high conditional beta have strong attention-grabbing characteristics, leading to a higher fraction of buyer-initiated trades for these stocks. We also find that stocks recently bought perform significantly better than stocks recently sold. Hence, the high beta stocks that investors are more likely to buy have higher expected returns than the low beta stocks that investors are more likely to sell. This paper was accepted by Lauren Cohen, finance.